Molting process revealed by the detailed expression profiles of RXR1/RXR2 and mining the associated genes in a spider mite, Panonychus citri. (9th September 2021) - Li, Gang; Liu, Xun‐Yan; Smagghe, Guy; Niu, Jin‐Zhi; Wang, Jin‐Jun
Abstract: Spider mites have one ecdysone receptor (EcR) and multiple retinoid X receptors (RXRs). However, the function of these RXRs in spider mite development is unknown. Here, we screened the expression dynamics of two PcRXR isoforms at 4 h intervals in the deutonymphal stage of Panonychus citri . The results showed that PcEcR had an expression pattern similar to that of PcRXR2 . For PcRXR1, its expression remained at a certain high level, when there was a decrease of both PcEcR and PcRXR2 . In situ hybridization showed that PcRXR2 was detected in the central nervous mass, while the ecdysteroid biosynthesis gene PcSpo was mainly expressed at the edge of the central nervous mass. RNAi‐based silencing of PcRXR1 or PcRXR2 showed the same phenotype as in mites with that of silencing PcEcR . Furthermore, RNA‐seq was used to mine the genes associated with the expression dynamics of PcRXR1 or PcRXR2, which revealed that the heterodimer of EcR‐RXR2 in spider mites might be linked with the cell autophagy and tissue remodeling during apolysis, and RXR1 might be linked with new epicuticle and exocuticle secretion during ecdysis. Taken together, these results increase our understanding of the regulation mechanism of ecdysteroid signal pathway in spider mite development. Abstract : Spider mites have one ecdysone receptor (EcR) and multiple retinoid X receptors (RXRs). However, the function of these RXRs in spider mite development is unknown.